TEACHING BUSINESS ENGLISH TO STUDENTS: CONCEPT OF ENGLISH FOR BUSINESS PURPOSES (EBP) AND ENGLISH FOR BUSINESS COMMUNICATION (EBC) - Fitria, Tira Nur (Universitas Bunda Mulia, 2025)
This study describes Business English skills (reading, writing, speaking, and listening) and exploring strategies for integrating those skills into economics education, thereby providing a comprehensive approach to preparing students for successful communication and negotiation in global business contexts. This study employed a library research approach to gather comprehensive literature relevant to the integration of teaching Business English into English skills (reading, writing, speaking, and listening) for economic students. The analysis shows that Business English is specialized for international business contexts, aiming to improve communication through emails, presentations, and negotiations. It enhances professional interactions by developing skills in business vocabulary, writing, listening, speaking, and cross-cultural understanding, preparing individuals for diverse global career opportunities. Teaching materials are tailored to these goals, focusing on technical terminology, business report writing, and practical application in scenarios like financial reports and project proposals. They employ activities such as presentations, discussions, and simulations to foster communication skills and critical thinking. This approach promotes active learning through engagement in real-world applications, ensuring learners are prepared for success in the competitive global business environment. Teaching Business English to economics students focuses on developing reading, writing, listening, and speaking skills tailored for professional contexts. In reading, students analyze business documents like financial reports to extract critical information and master key terms for decision-making. Writing instruction emphasizes crafting clear and persuasive emails, reports, and proposals for effective communication. Listening skills prepare students to understand diverse accents in business conversations and presentations, enabling them to capture essential details and participate effectively. Speaking practice builds fluency and confidence in delivering presentations, negotiating, and engaging in discussions respectfully. Educators address challenges such as tailoring instruction to business needs, overcoming language difficulties, developing robust communication skills, integrating technology effectively, and fostering critical thinking and cultural sensitivity. By tackling these challenges, teachers enhance their strategies to prepare students for success in the global business environment.